Revisiting Indonesia’s Blue Economy Vision in IORA - Marie, Nurul Titi; Samhudi, Galby Rifqi; Handayani, Prawita Meidy (The Republic of Indonesia Defense University, 2024)
Indonesia utilizes the Blue Economy framework, which combines economic growth, environmental care, and social equity by leveraging its abundant ocean resources. To some extent, the Blue Economy could also positively contribute to Indonesia's maritime security architecture as it provides the capital to boost its maritime security apparatus. To achieve this purpose, Indonesia actively participated in the Indian Ocean Rim Association (IORA), particularly after 2015, when the country led the organization and delivered on its vision of being the Global Maritime Fulcrum a year before. However, Indonesia’s Blue Economy initiative through the IORA appeared to be ineffective in resolving maritime challenges at the national level. Furthermore, its emphasis on an ocean-centric strategy for economic development is hampered by a half-hearted government that inconsistently supports the idea of a global maritime fulcrum. This study seeks to revisit Indonesia’s Blue Economy through involvement in the IORA. In addition, this study used the qualitative method to examine the difference between the IORA’s visions, the Blue Economy, and Indonesia’s Global Maritime Fulcrum. This study discovers that Indonesia’s involvement in the IORA does not successfully assist the country in expanding its marine sector, and it also experiences a divergence in the maritime-centric approach to development.